New Dacron tissue colonisable keratoprosthesis: clinical experience. Issue 9 (September 1995) - Pintucci, S; Pintucci, F; Cecconi, M; Caiazza, S
Abstract : BACKGROUND–Keratoprostheses (KPs) are made of an optical cylinder integrated with a supporting element which conditions their biocompatibility. A new KP with a Dacron tissue colonisable support has been designed in order to reduce significantly the complication rate. METHODS–This new KP was implanted into 20 eyes of 20 patients with bilateral corneal blindness unsuited to a corneal implant. The follow up ranged from 24 to 96 months. RESULTS–All 20 patients had some improved visual acuity with 13 retaining this improvement for more than 2 years. CONCLUSION–These favourable results may be indicative of the reliability of the new KP.